Pengaruh Follow The Bible, Prayer Band, dan Worship Terhadap Akhlak Peserta Didik Kelas 12 di SMA UNKLAB Airmadidi - Alfrits Reky Sambur; Alvyn Hendriks; Stimson Hutagalung; Rolyana Ferinia (Peneliti.net, 2022)
The purpose of this study is to determine the effect of the variabel follow the bible, prayer band, and worship on students' moral. This study uses a quantitative method with an explanatory approach. Technique collection data is used a questionnaire. The data analysis technique used simple regression analysis to see the effect partially and multiple regression analysis to see the effect simultaneously. There are four variables, namely follow the bible, prayer band, worship and students’ morals. The subjects used in this study were grade 12 students at SMA UNKLAB Airmadidi, district of Minahasa Utara, province of Sulawesi Utara. The results found that partially it is proven that there is an effect of the follow the bible (X1) and prayer band (X2) variabels on the students' moral variabel (Y). While the variabel worship (X3) have no effect on students’ moral. Other than, that all variabels, are follow the bible, prayer band, and worship simultaneously affect the students' moral. The conclusion is, Follow the Bible activities that are carried out consistently contribute to the morals of students. Furthermore, prayer bands activities carried out at school regularly also contribute to the morals of students. As for worship activities, even though they are carried out regularly, they do not make a significant contribution to the morals of students. For all variables, namely follow the bible, prayer, and worship which are carried out consistently, together they contribute to the morals of students.